Proceedings of the fourth international forum on decision sciences. - LI, XIANG (SPRINGER Verlag, SINGAPOR, 2017)
These conference proceedings focus on the topics of data-driven decision-making, stochastic decision-making, fuzzy decision-making and their applications in real-life problems. Beijing University of Chemical Technology organized IFDS2016, the 4th International Forum on Decision Sciences, with the theme "Data-Driven Decision-Making." The proceedings collect 84 selected papers presenting cutting-edge modeling and solution methods and include numerous practical case studies, making it a valuable resource for students, researchers and practitioners working in the fields of decision science, operations research, management science and engineering.
Keywords: Decision making -- Mathematical models -- Congresses.; elektronické knihy; electronic books